Effect of Consular Service in The Relationship Between Remittances, Skills & Knowledge, Technology, Investment and National Development – A Case of Kenya - Kipkazi, Kiprop Cyrus; Vasudevan, Hemaloshinee; VENUGOPAL, Panjavarnam (International Journal of Contemporary Economics and Administrative Sciences, 2024)
The diaspora is widely recognized globally as a key contributor to economic growth. The Kenyan government’s economic development plan, Kenya Vision 2030, acknowledges the significant role of the diaspora in the country’s economic growth and national development. As a result, policymakers are increasingly focusing on the Kenyan diaspora. They have been instrumental in promoting skills, knowledge, and technology transfer to Kenya. This study analyzes how consular services facilitate the relationship between remittances, skills, technology, investment, and national development. This study used a questionnaire survey to gather data from the Foreign Service cadre staff of the Ministry of Foreign Affairs in Kenya. 80 out of 100 questionnaires were returned and found usable. The study showed that there are 800 staff members in this cadre. Non-probability convenience sampling was employed. The data was analyzed using SPSS and Smart PLS. The study revealed the significant roles played by network theory and institutional theory in contributing to national development by the Kenyan diaspora. After testing eleven hypotheses, five were accepted (p-values 0.0000 to 0.0400), while six were not supported (p-values 0.196 to 0.646). It was due to the limited understanding and lack of acceptance of the need to improve the quality of consular services among the respondents. The study empirically confirms the pivotal role played by consular services in increasing dialogue between diplomatic missions and the diaspora and tapping into the underutilized potential of the diaspora in national development by developing investment-friendly policies targeting remittances and creating a platform for the transfer of skills, knowledge, and technology back to Kenya.